The Impact of Digital Marketing Techniques on Brand Image: An Analysis of Conversion Rate Optimization in Jordan’s Banking Sector - Al Khaldy, Ibrahim Ali; Hindieh, Ayman; qurneh, Majed; Shkeer, Amged S; Samarah, Tariq Ali (Journal of Ecohumanism, 2024)
Current study aimed at examining the influence of conversion rate optimization (CRO) as a digital marketing techniques (A/B Testing, Landing Page Optimization, User Experience (UX) Optimization, Clear Call-to-Action (CTA), Social Proof, Simplified Checkout Process) In enhancing the brand image from perspective of customers in Jordan banks sector. Quantitative methodology was adopted, and a questionnaire was self-administered by (100) customers. Results of study indicated thatconversion rate optimization (CRO)are able to enhancing the brand image with special influence of the variable (Simplified Checkout Process) as it has the ability to influence customer intention to make a purchase decision from a specific website based on the level of purchase process easiness and smoothness. This current study sheds the light on the relationship between conversion rate optimization (CRO) as a digital marketing techniquesand the concept of brand image, in addition to identify the best and most suitable digital process to optimize conversion rate.a